Meta-analysis of the efficacy of rituximab in the management of cryoglobulinemic vasculitis - Zhou, Ling; Dong, Jianxia; Deng, Zehui; Wang, Shaojuan; Fu, Mengjie; Peng, Jingjing; Zhang, Jian (Frontiers in Medicine, 2025)
IntroductionA primary goal of this study was to systematically assess the efficacy of rituximab (RTX) in treating cryoglobulinemic vasculitis (CV).MethodsA prospectively registered meta-analysis was conducted to examine eligible randomized controlled trials (RCTs) or cohort studies through searches across PubMed, Embase, Cochrane Library, and Web of Science, with a search period up to February 12, 2025. Data analysis was conducted utilizing STATA 16.0.ResultsIncorporating data from 12 studies involving 287 patients, CV patients who received RTX therapy demonstrated notable complete clinical response outcomes (Rate = 0.67, 95% confidence interval (95%CI): 0.61, 0.73) and a good clinical response rate. In addition, patients showed significant relief in symptoms such as skin purpura and skin ulcer (Rate = 0.92, 95%CI: 0.86,0.98). The meta-analysis findings indicated a notable enhancement in serum C4 levels in CV patients following treatment (mean difference (MD) = 0.06, 95%CI: 0.04, 0.07), both at 6-month (MD = 0.07, 95%CI: 0.05, 0.09) and 12-month (MD = 0.07, 95%CI: 0.03, 0.11) follow-ups. These findings suggest a gradual improvement in the underlying condition. The levels of IgM were significantly reduced following treatment (MD = −0.48, 95%CI: −0.65, −0.31), both at 6-month (MD = −1.05, 95%CI: −1.57, −0.52) and 12-month (MD = −0.59, 95%CI:−0.80, −0.38) follow-ups. The levels of cryoglobulin were also decreased following treatment (MD = −0.53, 95%CI: −0.80, −0.26), both at 6-month (MD = −0.67, 95%CI: −0.99, −0.35) and 12-month (MD = −0.67, 95%CI: −1.15, −0.19) follow-ups. Similarly, rheumatoid factor (RF) levels significantly decreased after treatment (MD = −318.20,95%CI:−364.66,−271.73) and remained low at the 6-month follow-up (MD = −287.78, 95%CI:−511.58,−63.97).DiscussionThe meta-analysis supports the favorable clinical efficacy of rituximab in the management of CV patients. However, further validation through additional high-quality RCTs is warranted to solidify its effectiveness.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024565790.